2023
DOI: 10.1038/s41467-023-41696-7
|View full text |Cite
|
Sign up to set email alerts
|

Regionally sourced bioaerosols drive high-temperature ice nucleating particles in the Arctic

Gabriel Pereira Freitas,
Kouji Adachi,
Franz Conen
et al.

Abstract: Primary biological aerosol particles (PBAP) play an important role in the climate system, facilitating the formation of ice within clouds, consequently PBAP may be important in understanding the rapidly changing Arctic. Within this work, we use single-particle fluorescence spectroscopy to identify and quantify PBAP at an Arctic mountain site, with transmission electronic microscopy analysis supporting the presence of PBAP. We find that PBAP concentrations range between 10−3–10−1 L−1 and peak in summer. Evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 83 publications
0
19
0
Order By: Relevance
“…This could result in an underestimation of the cell counts obtained from fluorescence microscopy. A number of previous studies have reported that microbes are more likely to be emitted attached to particles like SSA than as single cells. ,, Thus, the estimate from the MBS might be more appropriate with respect to atmospheric implications, e.g., when comparing to ice-nucleating particle (INP) concentrations, while the estimate from fluorescence microscopy is more applicable for single-cell analysis. In conclusion, given that there is only very little overlap in the sizing from both methods, they should not be compared and instead be considered complementary.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This could result in an underestimation of the cell counts obtained from fluorescence microscopy. A number of previous studies have reported that microbes are more likely to be emitted attached to particles like SSA than as single cells. ,, Thus, the estimate from the MBS might be more appropriate with respect to atmospheric implications, e.g., when comparing to ice-nucleating particle (INP) concentrations, while the estimate from fluorescence microscopy is more applicable for single-cell analysis. In conclusion, given that there is only very little overlap in the sizing from both methods, they should not be compared and instead be considered complementary.…”
Section: Resultsmentioning
confidence: 99%
“…The estimate from fluorescence microscopy is better suited for single-cell analysis, while that from the MBS (which can detect agglomerates of fluorescent particles within the detectable size range or if attached to slate particles, depending on the dynamics of the detection process) may be more appropriate when considering atmospheric implications, such as in comparisons with INP concentrations. 71 The MBS measurements revealed that fluorescent aerosol most consistent with PBAP constitutes only 4 out of 10 000 coarse SSA. This proportion is comparable to the concentrations of INPs found in remote marine regions, which make up approximately 1 in 10 5 −10 6 airborne particles.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We note that for E2 there is no bulk composition data from the ACSM available, and also for E1 the bulk composition is only partly available. In addition, due to instrumental issues, we are missing one additional BB event that was reported for July 2020 in a recent study by Yttri et al 52 and Freitas et al 53 The data in July only covers the first 3 days of the month.…”
Section: Overview Of the Biomass Burning Eventsmentioning
confidence: 99%
“…Therefore, it may be that in summer, terrestrial INP are collected from the surrounding land mass and is available, along with local, marine biological INP, for ice formation. Terrestrial INP have previously been found to be an important source of higher-temperature INP in the summertime Arctic (Pereira Freitas et al, 2023). In contrast, in winter, no such INP are available for either the MCAO or non-MCAO events when the air is advected over land, and therefore it takes time for the local INP to be transported from the ocean surface to the cloud layer in both cases.…”
Section: Effects Of Air Mass Historymentioning
confidence: 99%